Learning to love Form 1040 : two cheers for the return-based mass income tax - Zelenak, Lawrence (Chicago : The University of Chicago Press, 2013)
In this work, Lawrence Zelenak argues that filing taxes can strengthen fiscal citizenship by prompting taxpayers to reflect on the contract they have with their government and the value - or perceived lack of value - they receive in exchange for their money.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Income tax -- United States; Tax returns -- United States; Economics; United States of America, USA; Economics; Public finance & taxation; Jurisprudence & general issues